Patterns of weight loss and supplement consumption of male wrestlers in Tehran - Kordi, R.; Ziaee, R.; Rostami, M.; Wallace, W. A. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2011)
Background To evaluate the weight loss behavior of male wrestlers in Tehran.